Data-Driven Organization Design : delivering perpetual performance gains through the organizational system - Morrison, Rupert (London ; Philadelphia, PA : Kogan Page, 2021)
"Understand how to drive business performance with your organizational data and analytics in the second edition of Data-Driven Organization Design.Using data and analytics is a key opportunity for businesses to transform performance and achieve success. With a data-driven approach, all the elements of the organizational system can be connected to design an environment in which people can excel and attain competitive advantage. Data-Driven Organization Design provides a practical framework for HR and organization design practitioners to build a baseline of data, set objectives, carry out fixed and dynamic process design, map competencies, and right-size the organization. It shows how to collect the right data, present it meaningfully and ask the most relevant questions of it to help complex, fluid organizations constantly evolve and meet moving objectives. This updated second edition contains new material on organizational planning and analysis, role design and job architecture, position management lifecycle and delta reporting. Alongside this, new case studies and examples will show how these approaches have been applied in practice. Whether planning a long-term transformation, a large redesign or an individual small project, Data-Driven Organization Design will demonstrate how to make the most of your organizational data and analytics to drive business performance"--
Includes bibliographical references and index.
Keywords: Organizational effectiveness; Organizational change; Performance; Management -- Statistical methods